2019
DOI: 10.3390/ani9090602
|View full text |Cite
|
Sign up to set email alerts
|

Purified β-glucans of Different Molecular Weights Enhance Growth Performance of LPS-challenged Piglets via Improved Gut Barrier Function and Microbiota

Abstract: Simple SummaryBeta-glucan is currently under consideration as an alternative to in-feed antibiotics for the sustainable pig production industry in China. Modulating intestinal function by β-glucan treatment in young pigs is one potential way of decreasing disease susceptibility and presumably increasing growth performance. In the present study, as a newly developed commercial product, β-glucans have proved to modulate gut function, and have improved growth performance in lipopolysaccharide (LPS)-challenged pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…In addition, we did not find any significant differences in growth performance after 21 d feeding period between the olaquindox and the control group, however, pigs fed with β-glucan had greater BW and ADG than pigs in other groups. These results showed that β-glucan could improve the growth rate of weaned pigs, which was consistent with the previous study on LPS-challenged pigs ( Luo et al., 2019a ). However, no significant difference was found on growth performance between the olaquindox and the control group; the reason may be attributed to the feeding time (21 d) or dosage of the olaquindox in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we did not find any significant differences in growth performance after 21 d feeding period between the olaquindox and the control group, however, pigs fed with β-glucan had greater BW and ADG than pigs in other groups. These results showed that β-glucan could improve the growth rate of weaned pigs, which was consistent with the previous study on LPS-challenged pigs ( Luo et al., 2019a ). However, no significant difference was found on growth performance between the olaquindox and the control group; the reason may be attributed to the feeding time (21 d) or dosage of the olaquindox in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The villus height, crypt depth and villus height/ crypt depth values of the small intestine are important indicators of intestinal development and function. The increased crypt depth, lower villus height and villus height/crypt depth values in the small intestines of the LPS-stimulated group compared to the CON group were in accordance with recent researches Luo et al 2019). Moreover, previous research has demonstrated that feeding SB increased the jejunal villus height and villus height/ crypt depth (Wang et al 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The lactate and SCFA are recognized as beneficial metabolites of polysaccharides fermentation. β -glucan has been proved to have the potential to produce lactate, which could not only increase the content of lactate in the mucus of piglets but also provoke the growth of Bifidobacterium and the emergence of a balanced microbiota [ 37 ]. Besides, β -glucan oligosaccharides showed great lactate-producing capacity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%